Widespread low rates of Antarctic glacial isostatic adjustment revealed by GPS observations - Thomas, I.D. (author); King, M.A. (author); Bentley, M.J. (author); Whitehouse, P.L. (author); Penna, N.T. (author); Williams, S.D.P. (author); Riva, R.E.M. (author); Lavallee, D.A. (author); Clarke, P.J. (author); King, E.C. (author); Hindmarch, R.C.A. (author); Koivula, H. (author) (Geophysical Research Letters, 2011)
Bedrock uplift in Antarctica is dominated by a combination of glacial isostatic adjustment (GIA) and elastic response to contemporary mass change. Here, we present spatially extensive GPS observations of Antarctic bedrock uplift, using 52% more stations than previous studies, giving enhanced coverage, and with improved precision. We observe rapid elastic uplift in the northern Antarctic Peninsula. After considering elastic rebound, the GPS data suggests that modeled or empirical GIA uplift signals are often over?estimated, par t icularly the magnitudes of the signal maxima. Our observation that GIA uplift is misrepresented by modeling (weighted root?meansquares of observation?model differences: 4.9–5.0 mm/yr) suggests that, apart from a few regions where large ice mass loss is occurring, the spatial pattern of secular ice mass change derived from Gravity Recovery and Climate Experiment (GRACE) data and GIA models may be unreliable, and that several recent secular Antarctic ice mass loss estimates are systematically biased, mainly too high. Remote Sensing Aerospace Engineering